136 Initial experience of alemtuzumab for patients who fail natalizumab therapy. Issue 3 (9th February 2012) - Kelly, S; Duggan, M; Kinsella, K; Hutchinson, M; Tubridy, N; McGuigan, C
Abstract : Introduction: Patients with highly active MS who fail natalizumab therapy remain a challenge. Alemtuzumab, a monoclonal antibody targeting CD52 on lymphocytes, is available on a named-patient basis for such patients but it's efficacy and safety for this indication is not established. Methods: We performed a retrospective audit on patients receiving alemtuzumab after natalizumab therapy from July 2009 to January 2011. Results: Eleven patients received alemtuzumab after natalizumab. 3/11 had an allergic reaction to natalizumab and 8/11 failed treatment. Lymphopaenia developed 1 month after infusion in all patients. 4/11 developed leucopenia without neutropaenia within 3 months but normalised by 5 months. No serious infections were noted. 1/11 developed thyroid peroxidase antibodies at 3 months and biochemical hypothyroidism at 9 months post infusion. On prior treatment with natalizumab the annualised relapse rate was 2.5. In the year following alemtuzumab therapy this reduced to 0.1. Eight patients had an increased number of lesions, including four with gadolinium-enhancing lesions on MRI prior to alemtuzumab. Imaging 1 year after treatment did not identify any new T2 or gadolinium-enhancing lesions. Conclusions: From this limited experience alemtuzumab therapy appears to be well-tolerated and efficacious even for patients who have failed previous licensed therapies.